A three-headed plantaris muscle fused with Kaplan fibres: potential clinical significance - Maślanka, Krystian; Zielińska, Nicol; Paulsen, Friedrich; Niemiec, Małgorzata; Olewnik, Łukasz (Folia Morphologica, 2024)
The plantaris is a short, small muscle that usually originates at the popliteal surface of the femur and has a long, thin tendon that typically inserts into the calcaneal tuberosity. Its role and degree of development have been objects of debate for years. Some authors consider it a vestigial muscle while others believe it is a process of its development. The clinical significance of plantaris muscle is usually related to its morphological variation, which is common and well described in the literature. These variations are often a risk factor for many ailments and disorders. We would like to present another, very rare case of three-headed plantaris muscle (fused with distal Kaplan fibres), and consider what clinical implications it may have.
CRIS-Team Scopus Importer:2024-07-19
Keywords: development muscle; Kaplan fibres; knee stability; plantaris muscle; rudimentary muscle; three headed plantaris